Genetic profiling in radiotherapy: a comprehensive review - Rubini, Dino; Gagliardi, Federico; Menditti, Vittorio Salvatore; D’Ambrosio, Luca; Gallo, Paolo; D’Onofrio, Ida; Pisani, Antonio Rosario; Sardaro, Angela; Rubini, Giuseppe; Cappabianca, Salvatore; Nardone, Valerio; Reginelli, Alfonso (Frontiers in Oncology, 2024)
This comprehensive review explores the pivotal role of radiotherapy in cancer treatment, emphasizing the diverse applications of genetic profiling. The review highlights genetic markers for predicting radiation toxicity, enabling personalized treatment planning. It delves into the impact of genetic profiling on radiotherapy strategies across various cancer types, discussing research findings related to treatment response, prognosis, and therapeutic resistance. The integration of genetic profiling is shown to transform cancer treatment paradigms, offering insights into personalized radiotherapy regimens and guiding decisions in cases where standard protocols may fall short. Ultimately, the review underscores the potential of genetic profiling to enhance patient outcomes and advance precision medicine in oncology.